2003
DOI: 10.1200/jco.2003.04.040
|View full text |Cite|
|
Sign up to set email alerts
|

Docetaxel and Doxorubicin Compared With Doxorubicin and Cyclophosphamide as First-Line Chemotherapy for Metastatic Breast Cancer: Results of a Randomized, Multicenter, Phase III Trial

Abstract: AT significantly improves TTP and ORR compared with AC in patients with MBC, but there is no difference in OS. AT represents a valid option for the treatment of MBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
189
1
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(201 citation statements)
references
References 22 publications
4
189
1
7
Order By: Relevance
“…Recurrence-free survival was longer, 32 months, than the 18-19 months reported in retrospective series and the 20-26 months observed in randomized [17,19]. Our recruit ment bias might have had an effect here; the inclusion of wo men who had received at least three chemotherapy lines may have selected patients with less progressive disease, or who were at least more sensitive to treatment.…”
Section: Discussionmentioning
confidence: 66%
“…Recurrence-free survival was longer, 32 months, than the 18-19 months reported in retrospective series and the 20-26 months observed in randomized [17,19]. Our recruit ment bias might have had an effect here; the inclusion of wo men who had received at least three chemotherapy lines may have selected patients with less progressive disease, or who were at least more sensitive to treatment.…”
Section: Discussionmentioning
confidence: 66%
“…We identified 21 eligible studies, of which three are ongoing (Table 2) (Dieras et al, 1995;Bishop et al, 1999;Chan et al, 1999;Nabholtz et al, 1999Nabholtz et al, , 2003Sjostrom et al, 1999;Luck et al, 2000;Paridaens et al, 2000;Bonneterre et al, 2001Bonneterre et al, , 2002Bonneterre et al, , 2003Jassem et al, 2001;Zielinski et al, 2001;Biganzoli et al, 2002;Icli et al, 2002;Talbot et al, 2002;Bontenbal et al, 2003;Sledge et al, 2003;Goldhirsch, 2005;Heidemann, 2005). An additional two studies were identified but excluded: the status of one as a randomised trial was unclear (Gebbia et al, 2003), and the second randomised women to cease vs continue paclitaxel (Gennari et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In all, 10 trials had collected quality-of-life data, eight of which had reported results (Bishop et al, 1999;Chan et al, 1999;Nabholtz et al, 1999Nabholtz et al, , 2003Hakamies-Blomqvist et al, 2000;Kramer et al, 2000;Carmichael, 2001;Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003). The type of instrument used and the way in which quality of life was reported varied across trials, as did the completion rate by patients of quality-of-life instruments.…”
Section: Quality Of Lifementioning
confidence: 99%
“…I n clinical tr ials for metastatic b reast can cer, an ADR an d d ocetaxel ( DOC) combination t herapy is m uch m ore ef fective t han t he previous c ombination t herapies (i.e., ADR-cyclophosphamide and fluorouracil-ADR-cyclophosphamide) [2,3]. However, severe toxicities including m yelosuppression and cardiotoxicity limit the clinical use of ADR/DOC combination therapy in many patients with breast cancer [2][3][4].…”
Section: Introductionmentioning
confidence: 99%